2022
DOI: 10.5194/acp-2022-44
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of model and ground observations finds snowpack and blowing snow both contribute to Arctic tropospheric reactive bromine

Abstract: Abstract. Reactive halogens play a prominent role in the atmospheric chemistry of the Arctic during springtime. Field measurements and models studies suggest that halogens are emitted to the atmosphere from snowpack and reactions on wind-blown snow. The relative importance of snowpack and blowing snow sources is still debated, both at local scales and regionally throughout the Arctic. To understand implications of these halogen sources on a pan-Arctic scale, we simulate Arctic reactive bromine chemistry in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(171 reference statements)
0
2
0
Order By: Relevance
“…Chemical modelling can be particularly useful to study reactive bromine source mechanisms along with specific multiphase reactions (e.g. Marelle et al, 2021;Ahmed et al, 2022;Swanson et al, 2022;Wang and Pratt, 2017). However, as noted in Wang and Pratt (2017), there are few vertically (and horizontally) resolved observations that can be used to evaluate the modelling of different halogen compounds, making observations that can fill this knowledge gap particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modelling can be particularly useful to study reactive bromine source mechanisms along with specific multiphase reactions (e.g. Marelle et al, 2021;Ahmed et al, 2022;Swanson et al, 2022;Wang and Pratt, 2017). However, as noted in Wang and Pratt (2017), there are few vertically (and horizontally) resolved observations that can be used to evaluate the modelling of different halogen compounds, making observations that can fill this knowledge gap particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Recent modeling efforts have been most successful in reproducing the seasonal cycle of SSA mass concentrations observed at multiple polar sites with a blowing snow source and have found that blowing snow is the dominant source of SSA in polar regions during winter and spring (Huang & Jaeglé, 2017;Rhodes et al, 2017). Several studies have proposed that snow-sourced SSA likely plays an important role in polar tropospheric ozone and halogen chemistry through the release of active bromine in polar spring contributing to ozone depletion events (ODEs) (Choi et al, 2018;Huang et al, 2020;Kalnajs et al, 2013;Marelle et al, 2021;Swanson et al, 2022;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%